PROPOSED INTEGRATED MARKETING COMMUNICATION STRATEGY FOR PURU KAMBERA MUSLIM FASHION INDUSTRY (The Indonesian Journal of Business Administration, 2019)
Puru Kambera is one of the best hijab brands in the city of Bandung provide quality products and unique designs. As early as 2019 Puru Kambera corrected ineffective marketing communication, various consumers in choosing other hijab fashion brands affects fluctuations promotions that have not been effective so as to increase brand image. This research conducted several steps that summarized in the conceptual framework. By analyzing the business issue with internal analysis used Marketing Mix 4P and STP. Meanwhile, external analysis used Porter Five Forces, competitor analysis, and customers analysis. SWOT analysis and TOWS matrix are also used to develop the strategy. Using  two types of data, which are the primary data that collected from In Depth Interview and questionnaire, with secondary data that gathered from journals, books, internet, and internal company data. The result of the research is developing new marketing communication plan using marketing communication mix, which is advertisement, personal selling, sales promotion, public relation, and direct marketing. Puru Kambera also using electronic media and print advertising in promoting according to integrated marketing communication concept. The implamantation plan of the new strategy consist of a timeline activities, and a budget plan. The timeline activities consist of a more detailed set of what activities Puru Kambera needs to be done and the time it needs to be conducted, starting from July to December 2019. The budget plan details the total cost required by Puru Kambera to conduct the plan.Keyword: Marketing Communication Strategy, STP analysis,  Porter Five Forces, Competitor Analysis, SWOT Analysis